Tooth brushing: An effective oral hygiene measure - Bemhemba Iba; VE ADAMU (Orapuh, Inc., 2021)
Many people adopt tooth brushing as their primary method of oral hygiene. Tooth brushing is a mechanical means of eliminating microbial biofilm (dental plaque) from the oral cavity. Evidences have shown that dental plaque is implicated in the initiation and progression of the commonest oal diseases - dental caries and periodontal disease. If dental plaque is actively eliminated from the oral cavity, the incidence of common oral diseases will be reduced. Dental authorities posit that using the 'ideal' tooth brush, supplemented with fluoride-containing tooth paste, at least, 2 times a day for about 2-3 minutes per session, with the right technique, will effectively eliminate material alba and dental plaque from the mouth. This review was intended to take a brief look at the concept of tooth brushing as an effective oral hygiene method. The review was carried out by taking a look at journal articles and related researches and reviews. It began with an introduction and proceeded to discuss thematic issues on tooth brushing in oral hygiene before drawing a conclusion that buttresses the strategic role of tooth brushing as an oral hygiene method in the control of dental plaque.